HOST-PARASITE COEVOLUTION: BONG JOON-HO’S URBAN SMELLSCAPES AND CONTAGIOUS TOUCH - JURIŠIĆ, Paula (International Journal of Korean Humanities and Social Sciences, 2021)
This paper is an exploration of some of the modes of haptic visuality, smell, touching, being touched and contagious contact in contemporary South-Korean cinema through Bong Joon-ho’s (봉준호) Oscar-awarded 기생충 (Gisaengchung, Parasite) (2019) and his earlier film 괴물 (Gwoemul, The Host) (2006), films that, I would argue, are the most prominent examples and a culmination of the embodied visuality within the contemporary South-Korean cinema. Both films operate as the studies of the internalized forms of capitalism, a phenomenon that, according to Bong Joon-ho (봉준호), “before it’s a massive, sociological term, is just our lives”. This paper looks into the manifestations of internalized capitalism in the everyday lives of Bong Joon-ho’s (봉준호) characters, as well as spatio-temporal structures that, I would argue, best reflect the process of internalization.